2006
DOI: 10.1038/sj.bjc.6603251
|View full text |Cite
|
Sign up to set email alerts
|

Dissemination of hepatocellular carcinoma is mediated via chemokine receptor CXCR4

Abstract: In different tumour entities, expression of the chemokine receptor 4 (CXCR4) has been linked to tumour dissemination and poor prognosis. Therefore, we evaluated, if the expression of CXCR4 exerts similar effects in human hepatocellular carcinoma (HCC). Expression analysis and functional assays were performed in vitro to elucidate the impact of CXCL12 on human hepatoma cells lines. In addition, expression of CXCR4 was evaluated in 39 patients with HCC semiquantitatively and correlated with both, tumour and pati… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

6
117
2
1

Year Published

2007
2007
2021
2021

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 153 publications
(128 citation statements)
references
References 26 publications
6
117
2
1
Order By: Relevance
“…A significant correlation was observed between CXCR4 expression, tumor progression, metastasis, and a decreased survival rate [80] . However, the lack of a loss of function mutation of the tumor suppressor gene p53 gene on CXCR4 expression in HCC indicated yet another unidentified mechanism [81] . However, an ambiguity as to whether CXCR4-CXCL12 actually promotes tumor growth as a downmodulation of CXCR4-CXCL12 expression in HCC, both in vitro and in vivo has been reported, where CXCL12/ CXCR4 also lacked an association with death and HCC recurrence [82] .…”
Section: Chemokine Ligand-chemokine Receptor Axismentioning
confidence: 99%
“…A significant correlation was observed between CXCR4 expression, tumor progression, metastasis, and a decreased survival rate [80] . However, the lack of a loss of function mutation of the tumor suppressor gene p53 gene on CXCR4 expression in HCC indicated yet another unidentified mechanism [81] . However, an ambiguity as to whether CXCR4-CXCL12 actually promotes tumor growth as a downmodulation of CXCR4-CXCL12 expression in HCC, both in vitro and in vivo has been reported, where CXCL12/ CXCR4 also lacked an association with death and HCC recurrence [82] .…”
Section: Chemokine Ligand-chemokine Receptor Axismentioning
confidence: 99%
“…Predictive systems that are developed will enable to accurately detect patients at high risk for early IHR, but there might be many problems to solve before these markers can be applied to daily clinical practice (Iizuka et al, 2004). Thus far, there have been few reports on a predictor for EHR after surgery, although several studies have identified several key genes or gene products related to distant metastasis (Schimanski et al, 2006;Iizuka et al, 2006b). It was reported that HCC recurred in distant organs in only 3 (7%) of 42 patients who underwent liver transplantation, a radical curative treatment strategies (Nart et al, 2003).…”
mentioning
confidence: 99%
“…With the inhibition of CXCR4, the growth and invasion could be impaired in some type of cancer cells (Muller et al, 2001;Ottaiano et al, 2005). Involvement of SDF-1/CXCR4 was reported during prostate cancer, ovarian cancer, colorectal cancer, hepatocellular carcinoma as well as pancreatic cancer (Hart et al, 2005;Jiang et al, 2006;Schimanski et al, 2006;Yoshitake et al, 2008). It was reported that CXCR4 was expressed at higher levels in pancreatic cancer cells and could influence the clinical outcome of PDA patients Billadeau et al, 2006).…”
mentioning
confidence: 99%